Fencing the forest: early use of barrier fences in Sami reindeer husbandry - Gudrun Norstedt; Anna-Maria Rautio; Lars Östlund (Rangifer, 2017)
Barrier fences are generally not considered to have been used in Sami reindeer husbandry in Sweden before the early 20th century. As a rule, they are thought to have been introduced with the transition from intensive to extensive herding that is assumed to have taken place at this time. However, in this study, we show that barrier fences were widely used in Gällivare, Jokkmokk and Arjeplog Municipalities from the mid-18th century onwards, especially in the forests. Until the early 20th century, these fences were built of local materials, mainly whole trees and boulders, and we therefore call them whole-tree fences. Some of the barrier fences were used during periods of loose supervision by herders who otherwise practised intensive methods, while others were built in a context of extensive herding, large herds and conflicts over land use. Extensive reindeer herding was thus practised in the area much earlier than usually presumed, and it overlapped with intensive herding in both time and space.